Heart of darkness and youth - Conrad, Joseph, 1857-1924. (London : Vintage Books, 2007)
The captain of a steam ship on the Congo River meets and observes Mr. Kurtz, the fabled chief of the Inner Station for the trading company on that river in 1890.
Reprint. Originally published in the collection: Youth and two other stories. Garden City, N.Y. : Doubleday, 1929.
Young Adult.
Young Adult
Keywords: Europeans -- Africa -- Fiction; Suffering -- Fiction; Parables